FORMING OF THE VALUED ATTITUDE TOWARD HEALTH OF MEDICAL STUDENTS IN THE CONDITIONS OF EDUCATIONAL PROCESS OF HIGHER MEDICAL EDUCATIONAL ESTABLISHMENT - Skrinnik, E.А. (World of Medicine and Biology, 2018)
The peculiarities of the formation of the value attitude to the health and healthy lifestyle of medical students in the conditions of the educational process of the higher medical educational establishment are determined. The content of the notions of the value of health and the value of a healthy lifestyle is disclosed. The importance of axiology, deontology, valeology and physical education in the training of future doctors has been determined. The article identifies that the educational process in higher medical educational establishment aims to help students acquire theoretical knowledge of subjects, additional courses and acquiring practical skills necessary for professional activities. An important step in the training of future doctors is the process of formation of personal and professional qualities, principles and values. Undoubtedly, the leading role is the formation of values of health and healthy lifestyle of medical students. Therefore, along with the problems of improving the training of medical students from professional disciplines and practices, should be the task of increasing the level of spiritual and moral education, in particular the formation of value attitude to health. The main condition for the solution of this question is to deepen the knowledge axiology, deontology, valeology and physical education. In general, the process of formation of value attitude to health of medical students should include courses in physical education (general physical exercises, participation in sports clubs, contests), thematic educational events, lectures about the negative impact of bad habits, using the experience of pedagogical ethics, in-depth study of valeology, the use of innovative healthy saving and preventive technologies mentioned in the article. It was found that the formation of value attitude to health of medical students will have a positive impact on the results of educational-cognitive activity, because future doctors are required to learn quite a large amount of information. An important role in the educational process of training of medical students, playing the classes in physical education, which is one of the main tools in the formation of values of health and healthy lifestyle, focused on the improvement of psychophysical condition of students and the prevention of physical inactivity.
Keywords: formation of values; values of health; value of healthy lifestyle; medical students; educational process; training; higher medical educational establishment